Maternal presence facilitates plasticity in offspring behavior: insights into the evolution of parental care. (29th September 2018) - Munch, Kirke L; Noble, Daniel W A; Budd, Luke; Row, Aryana; Wapstra, Erik; While, Geoffrey M
Abstract : Using a family-living lizard, we show that the presence of a parent can have significant consequences for offspring behavior. Specifically, offspring were more bold, active, and exploratory with their mother compared with offspring who were alone. Offspring who developed with their mother also learnt quicker. These results show that even simple forms of parental care have significant consequences for offspring behavior and fitness providing novel insights into the early evolution of parental care. Abstract: Fundamental to the definition of parental care is that care confers benefits to the offspring. However, the mechanisms resulting in these benefits remain poorly understood, particularly in species where postnatal care is not obligatory. Here, we address this shortcoming using a lizard, Liopholis whitii, in which family life is facultative and relatively simple—extending to prolonged associations between parents and offspring within the parental territory. Using a split-clutch design, we housed offspring either with their mother or alone during the first 8 weeks of postnatal life and examined whether maternal presence affected 1) the expression of key functional behaviors and 2) learning ability in a biologically relevant antipredatory task. We found that offspring housed with their mothers expressed heightened levels of activity, boldness, and exploration compared with offspring who were housed alone. Furthermore, we show that associating with mothers during early postnatal periods led to improved offspring performance in the antipredation learning task. Together these results suggest that even relatively simple forms of enhanced parent-offspring association can have significant impacts on offspring traits. We argue that such effects may help refine and stabilize parent–offspring associations early in their evolution, potentially setting the stage for the elaboration of both parent and offspring behaviors.